The Evolution of the German Tort Law in the 19th Century - An Economic Analysis of the Evolution of Law - Martina Eckardt (Universität Rostock, Institut für Volkswirtschaftslehre, 1999)
Despite the advances in New Institutional Economics about the economic consequences of institutions and legal rules, up to now we have only limited knowledge about the mechanisms of the evolution of law. By combining the main ideas of Evolutionary Economics and New Institutional Economics this paper tries to contribute to our understanding of the process of institutional innovations. It is shown that the decisive factors that explain legal change are (1) the cognitive creativity of the actors and (2) wealth effects caused by negative technological externalities, which result from the use of new technologies. The main focus is on the evolution of the German tort law in the 19th century beginning with the introduction of the strict liability rule for railway accidents by the Prussian Railway Law in 1838. This was a complete break with the whole German tradition of tort law which was firmly based for centuries on the negligence rule. This case study shows how the co-evolution of technical and legal changes triggered off a trial-and-error-process of legal innovations and imitations that resulted in the present-day broad diffusion of the liability rule in the German tort law.
Keywords: D72; K13; N43; O31; 330; Evolutionary Economics; New Institutional Economics; Economic Analysis of Law; Haftung; Rechtsökonomik; Evolutionsökonomik; Institutioneller Wandel; Deutschland